Molecular characteristics of pepsinogen and pepsin from duck glandular stomach - Pichová, I; Kostka, V (Comparative biochemistry and physiology. B, Comparative biochemistry, 1990)
1. Two procedures were developed for the preparation of duck pepsinogen, an enzyme from the family of aspartic proteases (EC 3.4.23.1) and its zymogen. 2. The amino acid composition, sugar content and the partial N- and C-terminal sequences of both the enzyme and the zymogen were determined. These sequences are highly homologous with the terminal sequences of chicken pepsin(ogen). 3. Duck pepsinogen and pepsin are unlike other pepsin(ogen)s in being relatively stable in alkaline media: pepsinogen is inactivated at pH 12.1, pepsin at pH 9.6. 4. Duck pepsin is inhibited by diazoacetyl-D,L-norleucine methyl ester (DAN), 1,2-epoxy-3(p-nitrophe-noxy)propane (EPNP), pepstatin and a synthetic pepsin inhibitor Val-D-Leu-Pro-Phe-Phe-Val-D- Leu. The pH-optimum of duck pepsin determined in the presence of synthetic substrate is pH 4. 5. Duck pepsin has a marked milk-clotting activity whereas its proteolytic activity is lower than that of chicken pepsin. 6. The activation of duck pepsinogen is paralleled by two conformational changes. The activation half-life determined in the presence of a synthetic substrate at pH 2 and 14 degrees C is 20 sec.
Keywords: Molecular Sequence Data; Sequence Homology, Nucleic Acid; sekvence aminokyselin; Pepsinogens; pepsinogeny; pepsin A; Pepsin A; Enzyme Activation; Protein Conformation; žaludek ptáků; zvířata; Amino Acid Sequence; kachny; aktivace enzymů; Ducks; Chromatography, DEAE-Cellulose; sekvenční homologie nukleových kyselin; molekulární sekvence - údaje; Stomach, Avian; chromatografie DEAE-celulózová; konformace proteinů; Animals